"It's in My Blood": The Military Habitus of Former Zimbabwean Soldiers in Exile in South Africa. (January 2015) - Maringira, Godfrey; Gibson, Diana; Richters, Annemiek
This article examines the habitus of soldiers who either deserted or resigned from the Zimbabwe National Army in the post–2000 crisis in Zimbabwe and now live in exile in Johannesburg, South Africa. It is based on the information provided by forty-four former soldiers who related their life histories and participated in informal conversations and group discussions. A main finding is that these men, even though they have left the army, hold on in the extreme to their being as soldiers. This is shaped by at least four, interlinked dimensions of change in their lives: leaving the army without honorable discharge, leaving Zimbabwe itself, being exiles in an often unwelcoming South Africa, loss of family life and military status. The post-deployment dominance of military dispositions in the identity of the former soldiers is quite unique. Most former combatants worldwide have succeeded in different degrees to unmake their habituated forms of military identity or live with multiple identities.